2014
DOI: 10.1186/1880-5981-66-89
|View full text |Cite
|
Sign up to set email alerts
|

Microchemical and structural evidence for space weathering in soils from asteroid Itokawa

Abstract: Here we report microchemical and microstructural features indicative of space weathering in a particle returned from the surface of asteroid Itokawa by the Hayabusa mission. Space weathering features include partially and completely amorphous rims, chemically and structurally heterogeneous multilayer rims, amorphous surface islands, vesiculated rim textures, and nanophase iron particles. Solar-wind irradiation is likely responsible for the amorphization as well as the associated vesiculation of grain rims. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
44
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 28 publications
6
44
1
Order By: Relevance
“…Asteroidal materials occurring as meteorites have been studied in detail. In particular, those recovered from the asteroid Itokawa by the Hayabusa spacecraft have been subjected to comprehensive studies (e.g., Nakamura et al 2011;Noguchi et al 2011Noguchi et al , 2014aNoguchi et al , 2014bNagao et al 2011;Tsuchiyama et al 2011;Yurimoto et al 2011;Nakamura et al 2012;Harries and Langenhorst 2014;Keller and Berger 2014;Langenhorst et al 2014;Mikouchi et al 2014;Thompson et al 2014;Takeda et al 2015). In contrast, it is difficult to obtain samples identified to be cometary in origin, with the exception of direct sampling by the Stardust mission that returned the dust samples from the short-period comet 81P/Wild 2 (Zolensky et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Asteroidal materials occurring as meteorites have been studied in detail. In particular, those recovered from the asteroid Itokawa by the Hayabusa spacecraft have been subjected to comprehensive studies (e.g., Nakamura et al 2011;Noguchi et al 2011Noguchi et al , 2014aNoguchi et al , 2014bNagao et al 2011;Tsuchiyama et al 2011;Yurimoto et al 2011;Nakamura et al 2012;Harries and Langenhorst 2014;Keller and Berger 2014;Langenhorst et al 2014;Mikouchi et al 2014;Thompson et al 2014;Takeda et al 2015). In contrast, it is difficult to obtain samples identified to be cometary in origin, with the exception of direct sampling by the Stardust mission that returned the dust samples from the short-period comet 81P/Wild 2 (Zolensky et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…They include impact cratering (e.g., Melosh, 1989 ), regolith formation (e.g., Melosh, 1989 ), regolith mixing, and migration (e.g., Robinson et al, 2001;Veverka et al, 2001;Miyamoto et al, 2007 ). In addition, microscopic meteoroid impacts contribute to changes in the optical properties, chemical composition, and structures of regolith surface material ( Noguchi et al, 2011;Harries and Langenhorst, 2014;Keller and Berger, 2014;Noguchi et al, 2014;Thompson et al, 2014;Bonal et al, 2015;Matsumoto et al, 2015;Harries et al, 2016;Matsumoto et al, 2016 ). In addition, regolith activity on Itokawaprobably driven by impact processes-has been identified based on grain motion ( Nagao et al, 2011;Matsumoto et al, 2016 ), fracturing ( Tsuchiyama et al, 2011;Langenhorst et al, 2014 ;Matsumoto et al, 2016 ), and abrasion ( Tsuchiyama et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mineralogical and oxygen isotope analyses revealed that the composition of the particles is consistent with LL5-6 chondrite composition Yurimoto et al 2011;Nakashima et al 2013). The return of the Hayabusa samples has provided us the strongest evidence that the most common meteorites in our collections, the ordinary chondrites, are derived from the S-type asteroids Thompson et al 2014). The Hayabusa samples are the second extraterrestrial regolith, after the lunar samples, which can give us information about surface modification processes on airless bodies such as energetic particle irradiation and micrometeoroid impacts.…”
Section: Introductionmentioning
confidence: 79%
“…The Hayabusa samples are the second extraterrestrial regolith, after the lunar samples, which can give us information about surface modification processes on airless bodies such as energetic particle irradiation and micrometeoroid impacts. The resulting optical, physical, and chemical effects of these processes are collectively known as space weathering (Clark et al 2002;Thompson et al 2014). Understanding space weathering on asteroids can connect remote-sensing observations with laboratory studies and can lead to a better understanding of the evolution of asteroid soils (e.g.…”
Section: Introductionmentioning
confidence: 99%